Time to Start Delivering Iron Chelation Therapy in Newly Diagnosed Severe β-Thalassemia. (14th December 2020) - Susanah, Susi; Idjradinata, Ponpon S.; Sari, Nur M.; Rakhmilla, Lulu E.; Sribudiani, Yunia; Trisaputra, Jessica O.; Moestopo, Octawyana
Abstract : Background . Iron overload is still a major complication of severe β -thalassemia. Indication to start iron chelation therapy is based on serum ferritin (SF) or transferrin saturation (TS) level or the amount of transfusion. The goal of this study is to analyse the pattern of iron status, the amount of transfusion regarding the time to start iron chelator, and serum hepcidin levels in newly diagnosed severe β -thalassemia. Methods . A prospective cohort study was performed at Hasan Sadikin General Hospital on newly diagnosed severe β -thalassemia patients. Subjects had not received any blood transfusion with normal liver function test, CRP, and IL-6 levels who consumed normal diet according to age. The SF and TS levels indicate iron status, while hepcidin level indicates iron regulator status. Main indicator to start iron chelation therapy when SF level ≥1.000 ng/mL, TS level ≥70%, or after receiving transfusion at least 10 times. Statistical analysis used Mann–Whitney and Spearman. Results . Forty-two newly severe β -thalassemia, 30 (71.4%), were diagnosed before 1 year old, mean 9.9 ± 6.4 months, range 2–24 months. Range amount of transfusion until SF level reached ≥1, 000 ng/mL were 4-12 times, mean 7 ± 2 times. Mean SF and TS level at diagnosis were 365.6 ± 194.9   ng / mL and 67.3 ± 22.5 %, while hepcidin level was normal, mean 242.6 ± 58   ng / mL . 36/42 patients have reached SF >1000 ng/mL with amount of transfusion less than 10 times. There was no significant difference of SF, TS, and hepcidin levels when SF >1000 ng/mL in the group with amount of transfusion 7–12 and less than 7 (p = 0.454, p = 0.084, p = 0.765 ), respectively. A significant positive correlation between SF and amount of transfusion was observed (p < 0.001 ; r = 0.781 ). Conclusion. Iron overload in severe β -thalassemia patients might occur earlier even before they received 10 times transfusion. Hepcidin serum level tends to increase when iron overload just started.